Intervensi tahu ungu mampu memperbaiki profil lipid darah subjek penderita diabetes melitus tipe-2 - Amrizal, Sri Novalina; Zakaria, Fransiska Rungkat; Chasanah, Ekowati; Suliantari, Suliantari (Jurnal Gizi dan Pangan, 2017)
This study aimed to determine the effect of purple tofu intervention made from black soybean seeds in improving blood lipid profile of diabetics. Intervention of purple tofu was performed for 28 days and 20 subjects selected purposively and divided into two groups, control and treated. Tofu was served in soup form as much as 85 g. Significant improvement was identified in blood lipid profile of subjects after intervention (p<0.05). Decreased lipid profile occurred in triglycerides, low density lipoprotein (LDL), total cholesterol, and high density lipoproteins (HDL) (175.60±72.61 mg/dl to 123.70±29.50 mg/dl; 133.76±47.00 mg/dl to 98.96±13.81 mg/dl; 207.00±52.26 mg/dl to 154.40±50.89 mg/dl; 48.90±3.24 mg/dl to 30.80±7.09 mg/dl, respectively). Overall, black soy improves blood lipid profile of type 2 diabetes mellitus subjects, involving decreased triglycerides, LDL, and total cholesterol levels, but has not been able to increase HDL levels.